Pengembangan Bahan Ajar Cerita Rakyat Daerah “Sosokan Taba” Berbasis Karikatur untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDN 03 Kepahiang - Lasmini, Levi; Muktadir, Abdul; Parmadi, Bambang (Jurnal Kajian Pendidikan Dasar, 2025)
The purpose of this study was to develop, describe the level of feasibility, find out the user's response and find out the effectiveness of the caricature-based local folklore "Sosokan Taba" to improve learning outcomes for fourth grade students at SDN 03 Kepahiang". The type of research used is research and development   (Research   and   development).   The   research   model   in   the development of teaching materials is the ADDIE model. The type of data used is quantitative  and  qualitative  data  using  instruments in  the  form of  interviews, needs  analysis  questionnaires,  questions,  expert  validation  sheets  and  user response questionnaires. Based on the results of the study it can be concluded that the teaching materials that have been developed are suitable for use as teaching materials in class IV Indonesian content. The results of expert validation were 0.93 from material expert validation and 0.94 from design expert validation, and 0.95 from linguist validation. The user response was very good because the results of the class IV teacher questionnaire analysis showed a percentage of 94% with very good criteria. Meanwhile, the responses from students obtained a percentage of 94% with very good criteria. The teaching materials developed are effective for improving  the  learning  outcomes  of  fourth  grade  students  at  SD  Negeri  03 Kepahiang. This is based on the results of the average value of the experimental class that uses cartoon-based teaching materials to obtain a value of 75.08 while the control class obtains a value of 72.5 so that there is a significant difference between the control class and the experimental class.